2021
DOI: 10.1038/s41598-021-94201-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of spatial and temporal modules in lower limb muscle activations during walking with simulated reduced gravity

Abstract: Gravity plays a crucial role in shaping patterned locomotor output to maintain dynamic stability during locomotion. The present study aimed to clarify the gravity-dependent regulation of modules that organize multiple muscle activities during walking in humans. Participants walked on a treadmill at seven speeds (1–6 km h−1 and a subject- and gravity-specific speed determined by the Froude number (Fr) corresponding to 0.25) while their body weight was partially supported by a lift to simulate walking with five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The extracted muscle synergies described the four usual phases of the running cycle, both in normogravity and in simulated hypogravity. In this sense, it has been reported that the postural and walking muscle synergies were consistent up to 0.25 g and 0.16 g, respectively 38,39 . This suggests that the training protocols that astronauts undergo in normogravity (on Earth) may be transferable to hypogravity (e.g., on the Moon or Mars) and vice versa.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The extracted muscle synergies described the four usual phases of the running cycle, both in normogravity and in simulated hypogravity. In this sense, it has been reported that the postural and walking muscle synergies were consistent up to 0.25 g and 0.16 g, respectively 38,39 . This suggests that the training protocols that astronauts undergo in normogravity (on Earth) may be transferable to hypogravity (e.g., on the Moon or Mars) and vice versa.…”
Section: Discussionmentioning
confidence: 79%
“…This suggests that the training protocols that astronauts undergo in normogravity (on Earth) may be transferable to hypogravity (e.g., on the Moon or Mars) and vice versa. However, it should be noted that three muscle synergies would be sufficient to account for the sEMG signals when walking in very low gravity (0.07 g), compared to four at higher gravities (from 1 to 0.16 g) 39 . Although the current study only examined the running muscle synergies at 0.6 g, which is far from the gravity of Mars and the Moon, it highlighted some adjustments in the motor modules and motor primitives that should be considered in anticipation for future space missions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study of the characteristics of the voluntary movement is of broad interest in multiple frameworks. However, an appropriate description of human movement requires taking into account multiple simultaneous interactions, 2 stemming from the coordinated activations of several musculoskeletal segments, 3,4 and resulting in complex patterns 5 . Such patterns are fine‐tuned, and also small changes can lead to physiologically relevant effects 6 .…”
Section: Introductionmentioning
confidence: 99%